Biological control of coffee pest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Parasitic wasps found in East and West Africa have been introduced into Ecuador and Mexico to control the Coffee Berry Borer. The Borer has been spreading steadily through all the coffee-growing regions of the world and it is now a severe problem...